SHIFTING TRADITIONS OF PESANTREN IN SOUTH SULAWESI IN THE MODERN ERA: A PERSPECTIVE ON THE PESANTREN LAW - Andy, Andy; Khaerunnisa, Khaerunnisa; Nisa, Akramun (Idaarah: Jurnal Manajemen Pendidikan, 2024)
This study aims to analyze the shifting traditions of pesantren in South Sulawesi in the modern era, emphasizing the implementation of the Pesantren Law. The research employs a qualitative approach with a case study method, involving interviews, participant observation, and document analysis. The findings reveal that modernization has influenced the curriculum, pesantren management, and daily educational practices. Pesantren has integrated religious education with general education, adopted professional management practices, and utilized technology in learning. However, they uphold traditional values such as studying kitab kuning and character education. The Pesantren Law provides legitimacy, legal support, and access to resources, although adaptation to modernization faces challenges such as internal resistance and resource limitations. The study concludes that pesantren have successfully adapted to modernity without losing their traditional identity. The implication is that strengthening the implementation of the Pesantren Law is essential to maximize Pesantren’s role in fostering inclusive and adaptive Islamic education amid globalization.